Video-Assisted thoracoscopic surgery for pediatric empyema by two-port technique: A single-center experience with 167 consecutive cases - Sandesh V Parelkar; Shalil H Patil; Beejal V Sanghvi; Rahul Kumar Gupta; Satej S Mhaskar; Rujuta S Shah; Pooja Tiwari; Arjun A Pawar (Wolters Kluwer Medknow Publications, 2017)
Background/Purpose: The aim of our study is to determine efficacy, safety, and feasibility of video-assisted thoracoscopic surgery (VATS) in childhood empyema with a technique of only two ports and open instruments at a tertiary care center in India. Methods: This is a retrospective study of patients below 18 years, with empyema presenting to the Department of Pediatric Surgery of a Tertiary Care Referral Hospital in India, over a period of 9 years who underwent VATS decortication. Only two ports with open surgical instruments were used. The patients were assessed on the basis of mean duration of preoperative symptoms, duration of surgery, average blood loss, postoperative pain relief, complications, and need for redo surgery. Results: A total of 97 patients underwent primary VATS decortications without inserting an intercostal drainage (ICD) tube and 70 patients as a secondary procedure after ICD tube was inserted. Mean duration of symptoms was 11 days. The average blood loss during surgery was estimated to be 170 cc. The mean duration of surgery was 90 min. The most common postoperative complication was air leak seen in 19.16% of patients. Minor leaks usually settled by 24 h. In eight patients, a negative suction had to be applied to the ICD tube for persistent air leak. The average length of postoperative stay was 4 days. Two patients required a repeat open decortication procedure due to nonresolution of symptoms and poor lung expansion after VATS. Patients had minimal pain and excellent cosmetic outcome after VATS. Conclusion: Two-port VATS decortication procedure is as feasible and effective as three-port procedure for decortication with better cosmetic result and pain relief.